0753 Psychometric Properties Of Youth Self-rating Insomnia Scale (ysis) In Chinese Adolescents. (12th April 2019) - Liu, Xianchen; Yang, Yanyun; Liu, Zhen-Zhen; Fan, Fang; Jia, Cun-Xian
Abstract: Introduction: Although several insomnia scales are available for adults, no insomnia scale has been specifically developed for adolescents. This study assessed the psychometric properties of the Youth Self-Rating Insomnia Scale (YSIS) in a large sample of Chinese adolescents. Methods: The YSIS consists of 8 items assessing insomnia symptoms and perception of sleep disturbance in the past month (See the Support below). Each item is rated on a 5-point scale. A sample of 11, 452 adolescents in China completed the YSIS and a structured questionnaire to assess sleep duration, sleep problems, hypnotic use, and behavioral/emotional problems. A subsample of 242 adolescents completed retest questionnaire 2 weeks later. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed. Results: The YSIS score ranged from 8 to 40 ( M =18.5, SD =6.5). Internal consistency reliability coefficient was .80 and 2-week test-retest reliability coefficient was .82. Both EFA and CFA yielded 2 dominant factors defined as insomnia symptoms and subjective sleep disturbance. The YSIS score was significantly correlated with short sleep duration, depression, attention problems, hypnotic use, sleep disordered breathing problems, and restless legs syndrome. Similar results were obtained between male and female adolescents. Conclusion: YSIS is a simple, reliable and valid scale for assessing an adolescent's perception of insomnia severity. Further research is warranted to assess its psychometric properties with clinical samples and non-Chinese adolescents. Support (If Any): YSIS: During the past month, A. How would you rate the quality of your sleep overall? Very good, Good, Fair, Poor, Very Poor B. How satisfied were you with your sleep overall? Very satisfied, Satisfied, Fair, Unsatisfied, Very unsatisfied C. Trouble falling asleep? 1=Never, 2=<1 time/week, 3=1-2 times/week, 4=3-5 times/week, 5=6-7 times/week D. Wake up frequently during the night? 1, 2, 3, 4, 5 E. Wake up very early and can't get back to sleep? 1, 2, 3, 4, 5 F. Do not get enough sleep? 1, 2, 3, 4, 5 G. Feel unrested and unrestored upon waking? 1, 2, 3, 4, 5 H. Sleep difficulties interfere with your daily activities? 1, 2, 3, 4, 5